Perubahan Sosial Masyarakat melalui Dakwah Persuasif - Khairi Syafri; Rudi Haryanto , (STAI Hubbulwathan Duri, 2021)
Da'wah is a process of delivering messages orally or directly to change human behavior for the better, the da'wah interpreter will deal with audience groups who have the same tendency, for that the da'wah interpreter can display the delivery of da'wah messages according to the needs of mad'u. This paper with library research method reveals about persuasive da'wah strategies in changing people's behavior (mad'u). Based on the results of the study, it was found that da'wah communication aims to form a social structure that is equipped with social norms and shape people's behavior as mad'u. In persuasive da'wah communication, it is necessary to pay attention to the principles of persuasive da'wah, namely qaulan layyinan, qaulan sadidan, qaulan maysuran, qaulan baligha, qulan ma'rufa, qaulan karima and the stages of change in mad'u namely their knowledge, attitudes, and behavior.